Genetic conservation in Parkia biglobosa (Fabaceae: Mimosoideae) - what do we know? - Lompo, D.J.-P.; Vinceti, B.; Gaisberger, H.; Konrad, H.; Duminil, J.; Ouédraogo, M.; Sina, S.; Geburek, T. (Walter de Gruyter GmbH, 2017)
The medicinal and food tree species Parkia biglobosa (Faba-ceae: Mimosoideae) is widespread in the Sudanian savannahs of sub-Saharan Africa, where it has a strong socio-cultural and economic importance. Populations of this species are highly threatened in large parts of its range due to over exploitation and environmental degradation. In the light of climatic changes, safeguarding the genetic diversity of the species is crucial to foster adaptation and to support its long-term survival. Genetic insight is also relevant to guide sustainable harvesting. This paper has the objective to review information on the species’ geographic distribution, reproductive biology, genetic characteristics and existing conservation practices, and to identify knowledge gaps to orientate future conservation and research focus. The literature review revealed that the species is mainly out-crossed and is pollinated by a diversity of vectors, including bats that allow long-pollen dispersal. When bats are absent, pollination is mainly carried out by honey bees and stingless bees and in such case pollen-mediated gene flow is relatively restricted. Data of a large-scale genetic study based on allozyme markers showing a moderate genetic differentiation among populations were reanalyzed using an inverse dis-tance weighted interpolation function. Three distinctive regions of diversity based on allelic richness and expected heterozygosity were identified. Finally, we discuss future chal-lenges for genetic conservation by emphasizing the need to use both neutral and adaptive markers in future research.